2016
DOI: 10.1111/gwat.12401
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Associated With Natural Methane Occurrence in the Appalachian Basin

Abstract: The recent boom in shale gas development in the Marcellus Shale has increased interest in the methods to distinguish between naturally occurring methane in groundwater and stray methane associated with drilling and production operations. This study evaluates the relationship between natural methane occurrence and three principal environmental factors (groundwater redox state, water type, and topography) using two pre-drill datasets of 132 samples from western Pennsylvania, Ohio, and West Virginia and 1417 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 34 publications
6
34
0
Order By: Relevance
“…On the other hand, many samples with low‐methane show some sulfate (Figure S17). Positive correlation of dissolved methane concentration with that of chloride (Figure S21 crossplot) was already suggested by the Piper diagram; correlation with sodium is also positive (Figure S22) and stronger than that with chloride, an observation previously made by Molofsky et al () in the Marcellus Shale area. A few water samples, including one with some methane (HS46, 0.15 mg/L C1, −65.6‰ C1), show higher Ca concentrations.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…On the other hand, many samples with low‐methane show some sulfate (Figure S17). Positive correlation of dissolved methane concentration with that of chloride (Figure S21 crossplot) was already suggested by the Piper diagram; correlation with sodium is also positive (Figure S22) and stronger than that with chloride, an observation previously made by Molofsky et al () in the Marcellus Shale area. A few water samples, including one with some methane (HS46, 0.15 mg/L C1, −65.6‰ C1), show higher Ca concentrations.…”
Section: Resultssupporting
confidence: 72%
“…Once it appeared that high‐dissolved methane water wells were clustered, additional sampling was conducted in and around the cluster in order to better define it. Wells were sampled only once, but recent studies on methane variability have suggested that, although indeed variable, methane concentrations do not change by orders of magnitude in a given well (Gorody ; Loomer et al ; Molofsky et al ; Smith et al ). The sampling occurred between February and June 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Although, it has been detected in water wells of the Pennsylvania region for centuries (Molofsky et al, 2011, 2016), the origin of methane in aquifers and groundwater has remained misunderstood and it is likely that methane in the aquifers originates from a range of sources (Breen et al, 2007; Osborn et al, 2011; Wilson, 2014). Methane carbon and hydrogen isotopic ratios are frequently used to determine the possible source of methane in environmental samples (Whiticar, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Natural hydrocarbon and gas seepages are common in the Pennsylvania region and occurrence of methane in water wells has been observed for centuries (Molofsky et al, 2011, 2016). Therefore, this study aimed to investigate methane cycling and related microbial communities in methane-containing aquifers of the Pennsylvania region (Tioga County), from methane origin to methane oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there has been much discussion on the potential role of hydraulic fracturing, and opinion is divided on whether or not this poses a significant risk (Howarth et al 2011;O'Malley et al 2016;Darrah 2018). There are many recent case studies investigating the sources of methane in groundwater aquifers near shale plays (Molofsky et al 2016;Zhang and Soeder 2016;Nicot et al 2017aNicot et al , 2017bZhu et al 2018). 57, No.…”
Section: Introductionmentioning
confidence: 99%